Arbuscular Mycorrhizal Fungi Regulate Flowering of Hyacinths orientalis L. Anna Marie - Q.-Sheng Wu, M.-Miao Xie (Emirates Journal of Food and Agriculture, 2018)
Arbuscular mycorrhizal fungi (AMF) represent positive effects on growth performance, nutrient absorption and stressed tolerance of host plants, whereas it is not clear whether AMF can affect flowering traits of ornamental plants. In this work, Diversispora spurca, D. versiformis, and Funneliformis mosseae were applied to rhizosphere of potted hyacinth (Hyacinths orientalis L. Anna Marie) plants. After four months of mycorrhizal inoculation, root could be colonized by exogenous AMF species, varied from 38% to 49%, whilst F. mosseae had the best mycorrhizal status. Out of these AMF species used, only F. mosseae-inoculated plants recorded greater raceme length and biomass production of single flowerlet, raceme, and flower stem. F. mosseae also induced the flowering earlier in 2 days and prolonged flowering time for 3 days. D. versiformis postponed 2 days for flowering. Mycorrhizal plants recorded considerably higher acetic acid (IAA) and zeatin riboside (ZR) levels in flowers, irrespective of AMF species. F. mosseae-inoculated plants had significantly higher methyl jasmonate (MeJA) concentrations in flowers than other AMF- or non-AMF-treated plants. These results thereby conclude that F. mosseae can be used to regulate flowering of H. orientalis L. Anna Marie, including flowering earlier and prolonging flowering time, which is closely associated with IAA, ZR and MeJA levels in flowers.